What drives TARGET2 balances? Evidence from a panel analysis. Issue 77 (January 2014) - Auer, Raphael A.
Summary What are the drivers of the large TARGET2 (T2) balances that have emerged in the eurozone since the start of the financial crisis in 2007? This paper examines the extent to which changes in national T2 balances can be statistically associated with cross‐border private capital flows and current account (CA) balances. In a quarterly panel spanning the years 1999 to 2012 and 12 countries, it is shown that while the CA and changes in T2 balances were unrelated until the start of the 2007 financial crisis, since then the relation between these two variables has become statistically significant and economically sizeable. This reflects the 'sudden stop' in private sector capital that had hitherto funded CA imbalances. I next examine how different types of private capital flows have evolved over the last few years and how this can be related to changes in T2 balances, finding some deposit flight by private customers, a substantial retrenchment of cross‐border interbank lending, and also an increase in bank's holdings of high‐quality sovereign debt. My first conclusion from this analysis is that since T2 imbalances were caused by a sudden stop and are unlikely to grow without bounds as eurozone CA imbalances are currently diminishing at a rapid pace, there is no evidence that the institutional set‐up of the European monetary union needs to be reformed fundamentally. My further conclusions relate to how the current system transfers risks across the currency union. Limiting or settling T2 balances are not viable options. Rather, policies must be geared to limiting the implicit risk transfer from the private to the public sector within T2 creditor nations, which is facilitated by the current system as it may change the incidence of euro break‐up risk. — Raphael A. Auer